2020
DOI: 10.1002/mds3.10116
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on smart stents with sensors: From conventional permanent to novel bioabsorbable smart stent technologies

Abstract: Percutaneous coronary intervention with the aid of cardiovascular stents is the widely used therapeutic procedure for treating occlusive vascular diseases associated with the plaque deposition inside blood vessels. In spite of the momentous evolution and innovations in the field of medical technologies as well as biomaterial science, cardiovascular stents are still associated with several limitations. The introduction of bare metal stents, which revolutionized the field of interventional cardiology, was later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 79 publications
(102 reference statements)
0
17
0
Order By: Relevance
“…In spite of all the clinical developments, the mechanical properties of stent metallic platforms are unable to adapt to the surrounding biological environment leading to adverse clinical complications such as ISR, stent thrombosis, and subsequent target lesion revascularization [25,26]. In a clinical study, involving 6555 patients with 16,482 DES, stent fracture was found to be more frequently observed after DES implantation and almost one-fourth of fractured stents were subjected to target lesion revascularization [27].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of all the clinical developments, the mechanical properties of stent metallic platforms are unable to adapt to the surrounding biological environment leading to adverse clinical complications such as ISR, stent thrombosis, and subsequent target lesion revascularization [25,26]. In a clinical study, involving 6555 patients with 16,482 DES, stent fracture was found to be more frequently observed after DES implantation and almost one-fourth of fractured stents were subjected to target lesion revascularization [27].…”
Section: Resultsmentioning
confidence: 99%
“…However, a postoperative complication in-stent restenosis (ISR) frequently occurs and is attributable to the formation of thrombosis, the proliferation of smooth muscle cells, and neointimal hyperplasia. [13] A novel, selfreported stent incorporates a pressure flow sensor and a cell detector to provide a predictive solution to impending vascular complications. More advanced reasons propose protein molecular sensors to detect the smooth muscle cells and clots in the vascular system, with the aim of overcoming in-stent restenosis from early detection [14] and even deliver appropriate drugs [15,16] In addition, such smart stents enable continuous monitoring and appropriate treatments like hyperthermia therapy [17] and drug delivery.…”
Section: State-of-the-art Cardiovascular Implants and Energy Requirem...mentioning
confidence: 99%
“…To guarantee the high PTE of MRC-WPT system, the consistency of resonance frequency is essential, as expressed in Equation ( 13) [159] f LC π = 1 2 r (13) where L and C are the self-inductance and parasitic capacitance of the resonant transmitter or receiver coils. In addition, the coils can be modeled by a series RLC circuit and the quality factor (Q) is given by Equation ( 14) [161]…”
Section: Mrc-wptmentioning
confidence: 99%
“…Their results showed that their method is applicable to wireless detection of stent conditions after implementation. Vishnu and Manisavagam [16] applied for a review on smart stents with sensors. They indicated stent endothelialization could be detectable by changing the resonance frequency of the sensor attached to the stent due to contact with endothelial cells and stent.…”
Section: Introductionmentioning
confidence: 99%